The use of a novel burn dressing out of bacterial nanocellulose compared to the French standard of care in paediatric 2nd degree burns – A retrospective analysis. Issue 6 (September 2022) - Luca-Pozner, V.; Nischwitz, S.P.; Conti, E.; Lipa, G.; Ghezal, S.; Luze, H.; Funk, M.; Remy, H.; Qassemyar, Q.
Highlights: Epicite Epicite hydro is equally effective as the current standard of care for 2nd degree burns in France when it comes to wound healing and occurrence of infection. Nanocellulose wound dressings for second degree burns allow a quicker hospital discharge in children. Pain management in children is of special importance: the use of nanocellulose wound dressings is less painful than the French standard of care. Abstract: Purpose: Paediatric burn care is a delicate discipline which benefits from special attention. Despite being highly effective, the current standard of care for second degree burns in the largest paediatric burn center in France – exposure to infrared light – involves long hospital stays, straining economic and professional resources, especially in times of a pandemic. The present study investigated this standard of care and compared it to the use of a bacterial nanocellulose dressing. Materials and methods: A retrospective analysis of two groups has been performed: the control group assessed thirty consecutive children treated with the standard of care, and the intervention group assessed thirty consecutive children treated with the bacterial nanocellulose dressing. Parameters evaluated were: healed wounds, additional treatments, rate of infections, hospital length of stay, pain experience and overall satisfaction. Results: The two groups did not differ significantly in terms of age and TBSA. A significant reduction in hospital length of stay (p < .001) and pain experience (p < .001) could be observed. In terms of healed wounds, additional treatments and infections, the two groups were equally matched (p > .05) with satisfactory results in both groups. Tendencies towards better results could be seen in the intervention group. Conclusion: The use of bacterial nanocellulose wound dressings is an important tool in the armamentarium of today's burn surgeons. Satisfying results were achieved, ameliorating burn care for children. Future studies are indicated to further support its value and assess the economic impact.